Gestión del suministro de medicamentos en el departamento de farmacia del Hospital Belén de Trujillo en el periodo mayo 2006 – marzo 2007 - Cueva Cachay, Victoria del Pilar (2007)
This report had as objective to determine characteristics of the managment of supply of medicines in the Pharmacy Department at Belen Hospital of Trujillo. It was worked with files inventories and consumptions, file reports and monthly kardex of the 36 plotters drugs during the period May 2006-March 2007, these dates were collected in spreadsheet Excel ® 2003 during and later of the work of collecting information. Percentage weighted average inventory change for a set of medicines plotters 0,011; Average% of the stock registers match physical conteos is 78.15; Percentage average of a set of non-expired medicines tracers available and finally 97.47 the average percentage of time shortages 4, 08. These result shows lack in the inventories, shortages and unavailability of medicines plotters in a few months